Penggunaan Tenaga Kerja Keluarga Petani Peternak Itik pada Pola Usahatani Tanaman Padi Sawah di Kecamatan Air Hangat Kabupaten Kerinci - Fatati Fatati (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2006)
The  research  was  aimed  to  find  out  the  labor  employment  from  farmer  and  duck veterinarian family at farmer working pattern of rice plantation at Air Hangat Regency. The research was held by using survey method. The samples were 3 villages which were taken by purposive sampling method with determined criterion that the villages have main effort at rice plantation  as well as feeding ducks as secondary effort. The villages are Koto Majidin  Hilir  Village,  Majidin  Mudik  Village  and  Tebat  Ijuk  Village.  While,  the respondents were the veterinarian who were chosen by using Simple Random Sampling Technique.  The  number  of  respondents  is  determined proportionally  based  on  the population number of ducks at each village; there were 20 respondents at Majidin Hilir village, 15 respondents at Majidin Mudik village and 10 respondents at Tebat Ijuk village. The total number was 45 respondents. The research period is based on Effective Working time  and  the  labors  are  counted  based  on  Man  Base  Labor.  Next,  the  collected  data  is processed descriptively. The research result showed that the number of family labor was 57,39  persons  per  plant  season,  while  the  family  labor  who  are  employed  was  50,69 persons per plant season. Thus the rest of family labor was 6,70 persons per plant season.